MADRASA TEACHER'S SWOT IN GROWING THE SPIRIT OF LEARNING FIQH IN MILLENIAL GENERATION IN TULUNGAGUNG - Muh Khoirul Rifa’i (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
In the learning process, passion and interest are one of the most important dynamic aspects. With enthusiasm and interest in students, learning results will be maximized. Thus, the teacher must know the form of enthusiasm and interest that how should be used to foster student enthusiasm for learning. Given that by providing enthusiasm and interest, students can develop activities and initiatives and can maintain perseverance in conducting learning activities and so students do not feel bored with the subject of Fiqh. These conditions will affect students' understanding of the subject of jurisprudence. If students truly understand and practice what is contained in it that is fiqh, then students will be able to carry out religious commands properly according to the commands of Allah SWT. Departing from the facts and descriptions above, the researchers are interested in studying and conducting research on